Competing Endogenous RNAs in Hepatocellular Carcinoma—The Pinnacle of Rivalry - Afify, Abdelrahman Yousry; Ibrahim, Salma Abdulmaqsoud; Aldamsisi, Mennah Hisham; Zaghloul, Mai Saad; El-Ekiaby, Nada; Abdelaziz, Ahmed Ihab (Seminars in Liver Disease, 2019)
The role of noncoding transcripts in gene expression is nowadays acknowledged to keep various diseases at bay—despite being referred to as “junk” DNA several years ago. Believed to be at the heart of multiple regulatory pathways, microRNAs (miRNAs) are small noncoding RNAs (ncRNAs) involved in posttranscriptional gene regulation. Recently, the discovery of ncRNAs that compete for shared miRNA pools has dimmed the light on the solo performance of miRNAs in genomic regulation. Indeed, several studies describe RNAs such as long noncoding RNAs, mRNAs, circular RNAs, pseudogenes, and viral RNAs as competing endogenous RNAs (ceRNAs) that sequester miRNAs, allowing for de-repression of downstream miRNA targets. Such integration between coding and noncoding transcripts forms complex ceRNA networks that when dysregulated lead to several diseases such as hepatocellular carcinoma. Here, the authors review perturbed ceRNA networks in hepatocellular carcinoma, describe the role of each in tumorigenesis, and discuss their various clinical implications.
Keywords: competing endogenous RNAs; microRNAs; hepatocellular carcinoma